Photoconductivity of heterojunction MEH-PPV / TiO2 nanocomposite thin films / Fazlinashatul Suhaidah Zahid - Zahid, Fazlinashatul Suhaidah (2010)
This paper investigates the photoconductivity of the heterojunction of MEH-PPV/TiO2 nanocomposite thin films by varying the weight ratio of TiO2 and was deposited on the glass substrates by using spin coating technique. The influence of the amount of TiO2 in the nanocomposite heterojunctions and photoconductivity as prepared blends compared to the single component of MEH-PPV was characterized by Voltage/Current (I-V) characterization in dark and under illumination, UV-VIS spectrophotometer and Field Emission Scanning Electron Microscopy (FESEM). The I-V measurements in dark and under illumination shows that the resistivity decreases and conductivity increases when the amount of TiO2 increases. While UV-VIS spectrophotometer measurements show the optical band gap increases when the amount of TiO2 increases. The FESEM images also show that the MEH-PPV/TiO2 particles uniformly shaped but there are some large clusters were observed between the surface nanostructures.